2020
DOI: 10.1038/s41419-020-03034-3
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal stem cells reverse EMT process through blocking the activation of NF-κB and Hedgehog pathways in LPS-induced acute lung injury

Abstract: Acute lung injury (ALI) is a pulmonary disorder, which can result in fibrosis of the lung tissues. Recently, mesenchymal stem cell (MSC) has become a novel therapeutic method for ALI. However, the potential mechanism by which MSC regulates the progression of ALI remains blurry. The present study focused on investigating the mechanism underneath MSC-reversed lung injury and fibrosis. At first, we determined that coculture with MSC led to the inactivation of NF-κB signaling and therefore suppressed hedgehog path… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
91
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 144 publications
(109 citation statements)
references
References 47 publications
(55 reference statements)
0
91
0
Order By: Relevance
“…In vitro, activation of LL29 pulmonary fibroblasts was suppressed by BM-MSC EVs and this was due to targeting of frizzled class receptor 6 ( FZD6 ) by EV miR-29b-3p, which was also shown to be required for the inhibition by BM-MSC EVs of bleomycin-induced pulmonary fibrosis in mice [ 83 ]. Exposure of LPS-treated MLE-12 type II alveolar epithelial cells to BM-MSC exosomes resulted in inactivation of the nuclear factor kappa-light-chain-enhancer of activated B cells (NF-κB) pathway, reversal of EMT due to targeting of Ikbkb by exosomal miR-182-5b, and ubiquitinylation of Ikbkb due to targeting of Usp5 by exosomal miR-23a-3p [ 84 ]. In a mouse model of silicosis, lung dysfunction and fibrosis were reduced by exosomes from human umbilical cord MSC (UMSC), which were also effective in decreasing collagen deposition in silica-exposed fibroblasts in vitro [ 85 ].…”
Section: Pulmonary Fibrosismentioning
confidence: 99%
“…In vitro, activation of LL29 pulmonary fibroblasts was suppressed by BM-MSC EVs and this was due to targeting of frizzled class receptor 6 ( FZD6 ) by EV miR-29b-3p, which was also shown to be required for the inhibition by BM-MSC EVs of bleomycin-induced pulmonary fibrosis in mice [ 83 ]. Exposure of LPS-treated MLE-12 type II alveolar epithelial cells to BM-MSC exosomes resulted in inactivation of the nuclear factor kappa-light-chain-enhancer of activated B cells (NF-κB) pathway, reversal of EMT due to targeting of Ikbkb by exosomal miR-182-5b, and ubiquitinylation of Ikbkb due to targeting of Usp5 by exosomal miR-23a-3p [ 84 ]. In a mouse model of silicosis, lung dysfunction and fibrosis were reduced by exosomes from human umbilical cord MSC (UMSC), which were also effective in decreasing collagen deposition in silica-exposed fibroblasts in vitro [ 85 ].…”
Section: Pulmonary Fibrosismentioning
confidence: 99%
“…This study suggested that MSC‐Es reduce IKKβ and also increase its ubiquitination, resulting in inhibition of the NF‐κB and the Hedgehog pathways, both playing a key role in the Epithelial‐Mesenchymal Transition (EMT) process of alveolar epithelial cells (AECs) that is closely related to pulmonary fibrosis. 82 Investigation on a mouse ARDS model treated by MSC‐Es, which was differentiated to produce neurotrophic and immunomodulatory factors (MSC‐NTF) showed a substantial reduction in IFN γ, TNFα, IL‐6, and RANTES (regulated on activation, normal T cell expressed and secreted). The oxygen saturation level also was improved significantly after 72 h post‐treatment.…”
Section: Mesenchymal Stem Cells‐derived Exosomes (Msc‐e) In Combating Covid‐19mentioning
confidence: 99%
“… 86 Xiao and colleagues have demonstrated the downregulation of the Ikbkb gene results in a significant decrease in the gene expression of IKKβ, leading to downregulation of ubiquitin‐specific peptidase (Usp) 5, a deubiquitinase that blocks IKKβ ubiquitination. 82 There are a limited number of clinical trials ongoing to assess the safety and efficacy of MSC‐E for the treatment of Covid‐19, despite promising results in preclinical studies (Table 2 ).…”
Section: Mesenchymal Stem Cells‐derived Exosomes (Msc‐e) In Combating Covid‐19mentioning
confidence: 99%
“… 27 Further, a previous study from our group has revealed that MSC-derived exosomes transfer miR-23a-3p, and miR-182-5p reverses the progression of LPS-induced lung injury by inhibiting NF-κB and Hedgehog pathways. 28 …”
Section: Msc-derived Exosomesmentioning
confidence: 99%